Enhancing brand trust through influencer marketing credibility, honesty and trustworthiness - A SOR theory application - Nor Irwani Abdul Rahman; Amalina Mursidi; Julinawati Suanda; Nurul Izyan Yasmin Mohd Rizal (Universiti Pendidikan Sultan Idris, 2025)
Indexed Publication (Tier 3)